The Influence of Service Quality, Product Quality and Promotion on Sales Volume at Jenggong Café - Fachrizal Mauludin Farichi; Mukhlis Mukhlis (Universitas Negeri Padang, 2025)
As lifestyles shift alongside broader social and economic developments, the business landscape also changes one sector notably influenced is the coffee industry. Given Indonesia’s relatively high level of coffee consumption, many entrepreneurs have seized the opportunity to establish coffee shops. However, to remain competitive, businesses need strategies that prioritize customer satisfaction. Customer satisfaction is shaped by how well services are delivered and how products meet the consumer expectation. the higher these qualities are perceived to be, the greater the potential for increased revenue. The present study explored the role of service quality, product quality, and promotion in driving changes in the sales volume. The study employs an associative quantitative approach, with the data collected from 100 respondents chosen through probability sampling technique at the Jagakarsa Seduh Coffee Shop. Data were analyzed using classical assumption tests, simple linear regression, correlation analysis, determination coefficient analysis, as well as partial and simultaneous hypothesis testing. The overall model is statistically significant, as evidenced by F-statistic of 96.052, which surpassed the critical threshold of 2.70 and was supported by a probability value of 0.000. Individual testing further confirmed that service quality (X1) exerts a significant effect, reflected by a t-statistic of 6.584 that exceeds the reference value of 1.664. Product quality (X2) yields a t value of 2.542 with significance 0.01. Promotion (X3) records a t value of 12.223 greater than 1.664 with significance 0.00.